Case Report: Bilateral adrenal hemorrhage in a patient with systemic lupus erythematosus and antiphospholipid syndrome - Wang, Yuwei; Jin, Di; Pang, Jiangang; Ju, Wenlong; Nie, Weiduo; Gao, Rui; Li, Sheng-Guang; Li, Ming (Frontiers in Immunology, 2025)
This case report describes a rare and life-threatening complication of bilateral adrenal hemorrhage (AH) in a 15-year-old female with overlapping systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS). The patient presented with prolonged abdominal pain, low-grade fever, and lower limb pain. Imaging revealed bilateral adrenal hemorrhages, while laboratory investigations confirmed triple-positive antiphospholipid antibodies (ACA-IgG, ACA-IgM, anti-β2 glycoprotein I) and SLE-related serological markers. Management involved dual-pathway therapy: immunosuppression (prednisone, hydroxychloroquine) for SLE and anticoagulation (low-molecular-weight heparin, warfarin) for APS. Despite initial improvement, adrenal insufficiency developed, requiring glucocorticoid replacement. Follow-up demonstrated stabilized clinical status and reduced adrenal lesions. This case underscores the diagnostic challenges of AH in SLE-APS overlap and emphasizes the necessity of combining immunosuppressive and anticoagulant therapies to address both autoimmune inflammation and thrombotic risks. Early recognition and multidisciplinary management are critical to prevent adrenal crisis and improve outcomes in such complex autoimmune-thrombotic pathologies.